The Million Dollar Mystery : Novelized from the Scenario of F. Lonergan - MacGrath, Harold, 1871-1932; Lonergan, F. (Salt Lake City, UT : Project Gutenberg, 2012)
"The Million Dollar Mystery" by Harold MacGrath and F. Lonergan is a novelized mystery tale written in the early 20th century. The story opens with a mysterious atmosphere, revealing the plight of a man in a carriage hastily departing from a secluded area, carrying a bundle that turns out to be a baby girl named Florence. The narrative contrasts the suspenseful beginnings, with Miss Farlow, the caretaker of a private school, discovering Florence abandoned on her doorstep and vowing to protect her until the child$1 (Bs mysterious benefactor returns. The opening of the book sets the stage for an intricate plot involving espionage, hidden identities, and danger. As Florence grows up, she remains unaware of her father's connection to a powerful secret society known as the Black Hundred, who are determined to regain control over him. The narrative introduces various characters, including Stanley Hargreave, a man on the run from his past, and others who will play pivotal roles in safeguarding or exploiting Florence. The mystery intensifies as Hargreave's past intertwines with Florence$1 (Bs present, hinting at conflicts and adventures to unfold as she makes her way to discover the truth about her father and her own identity. (This is an automatically generated summary.)s
Release date is 2012-03-14
Produced by Al Haines
Keywords: Detective and mystery stories